2002
DOI: 10.1089/152308602762197407
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Induces a Rapid and Transient Increase of Reactive Oxygen Species

Abstract: Vascular smooth muscle cells (VSMC) exhibit a hypertrophic and contractile response after angiotensin II (Ang II) treatment, and the NADH/NADPH oxidase-dependent synthesis of hydrogen peroxide (H(2)O(2)) seems to play a central role in these responses. Present experiments were designed to analyze the mechanisms responsible for the rapid changes induced by Ang II in the intracellular H(2)O(2) concentration in VSMC. Ang II induced a quick and transient increase of dichlorodihydrofluorescein (DCHF) fluorescence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…51 The transient elevation of F 2 -isoprostanes after Ang II has been described in cell culture and ex vivo and may suggest the induction of compensatory antioxidant mechanisms, such as increased expression of extracellular superoxide dismutase. 52,53 That Ang II and NE both increased concentrations of F 2 -isoprostanes concurs with the observations of Aizawa et al, 54 who reported that both Ang II and NE increased free plasma F 2 -isoprostanes in rats, but conflicts with data from other studies. 55 Nevertheless, the lack of effect of NE on PRA or aldosterone suggests that NE increased F 2 -isoprostanes independently of activation of the RAAS.…”
Section: Discussionsupporting
confidence: 77%
“…51 The transient elevation of F 2 -isoprostanes after Ang II has been described in cell culture and ex vivo and may suggest the induction of compensatory antioxidant mechanisms, such as increased expression of extracellular superoxide dismutase. 52,53 That Ang II and NE both increased concentrations of F 2 -isoprostanes concurs with the observations of Aizawa et al, 54 who reported that both Ang II and NE increased free plasma F 2 -isoprostanes in rats, but conflicts with data from other studies. 55 Nevertheless, the lack of effect of NE on PRA or aldosterone suggests that NE increased F 2 -isoprostanes independently of activation of the RAAS.…”
Section: Discussionsupporting
confidence: 77%
“…These observations indicate that O 2 Ϫ augments, or partly mediates, the responses to ANG II in SHR. The latter is supported by observations that ANG II stimulation led to increased lucigenin chemiluminescence, indicating elevated production of ROS in response to ANG II (37,45). In the study by Shastri et al (45), inhibition of the NO system, by either L-NAME or endothelial denudation, abolished the effect of tempol on the ANG II response.…”
Section: Discussionmentioning
confidence: 78%
“…As HMC release a great amount of active metabolites [20], a rather non-specific approach was selected, in which some pharmacological antagonists, including receptor antagonists for AII, platelet-activating factor and thromboxane A 2 , as well as a hydrogen peroxide scavenger, were used. The blocking concentrations of these antagonists were selected according to concentrations previously shown to be effective [23,36,37]. As shown in the Results section, losartan was the most efficient antagonist among those partially explain the observed results.…”
Section: Discussionmentioning
confidence: 96%